2011
DOI: 10.1159/000321392
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors in Chronic Pelvic Pain due to Endometriosis: A Comparative Study

Abstract: Background/Aims: This study compared women suffering chronic pelvic pain (CPP) secondary to endometriosis (n = 30) with women experiencing CPP due to either myofascial abdominal/pelvic pain (n = 70) or pelvic adhesions (n = 38) to determine if there are specific psychological variables uniquely associated with endometriosis. Methods: This is a cross-sectional study of 138 women drawn from a convenience sample of 192 consecutive women with CPP presenting for evaluation to a university hospital chronic pain clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 52 publications
1
29
0
4
Order By: Relevance
“…Another investigation found equivalent rates of depression and anxiety in subjects with CPP and migraine 21 , and two others found no differences when comparing CPP groups with different etiologies 27,37 .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Another investigation found equivalent rates of depression and anxiety in subjects with CPP and migraine 21 , and two others found no differences when comparing CPP groups with different etiologies 27,37 .…”
Section: Resultsmentioning
confidence: 95%
“…From these, five studies [24][25][26][27][28] used an observational descriptive design and the remaining 13 8,20,21,[29][30][31][32][33][34][35][36][37][38] used a case-control design. Most of the studies were conducted in the United States (n = 6) and Brazil (n = 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 A large 5-year Australian 12 exploratory study suggested that there might be an associated risk of endometriosis for those women who have worked as a flight attendant, service station attendant or health worker, particularly a nurse. However other findings 13 fail to support the presence of a unique psychological profile or even a disproportionate psychological disturbance in women with chronic pelvic pain due to endometriosis; in addition, no differences were obtained for ratings of depression, anxiety, mood factors or additional personality traits. These data suggest that, in general, when psychological disorders are observed in chronic pelvic pain patients, they most likely reflect the effects of chronic pain rather being causative of it.…”
Section: Epidemiologymentioning
confidence: 85%
“…These tools can help to identify psychological problems at early period that is crucial for understanding the development of acute pain into chronic and also possibly preventing its chronicity. Several studies considered psychological factors are contributors to patients' chronicity, but others did not find such a relationship (Roth et al, 2011a;Roth et al, 2011b;Roth et al, 2011c;Wallin et al, 2011;Xu et al, 2011). Various results in different studies questioned the real analgesic effect of psychological approaches in chronic pain management.…”
Section: Efficacy Of Psychological Analgesiamentioning
confidence: 99%